Produksi Senyawa Kuinina dengan Fermentasi Mikroba Endofit Tanaman Cinchona pubescens Vahl. - Esti Mumpuni; Herman Suryadi; Partomuan Simanjuntak (Fakultas Farmasi Universitas Pancasila, 2005)
This study deals with endophytic microbes, known as a potential source of secondary metabolites. The microbes (F) were isolated from Cinchona pubescens Vahl and fermented in Phoma media, observing the pH, biomass growth and secondary metabolites of alkaloids for 14 days. The result obtained showed that the pH was between 4 and 5, the biomass growth relative stable after 8 days and the production of alkaloids reached its maximum also after 8 days (32.81 mg/l).